2017
DOI: 10.1111/ecpo.12102
|View full text |Cite
|
Sign up to set email alerts
|

Police Violence and the Underreporting of Crime

Abstract: This paper examines the relationship between police violence and the reporting of crime. Utilizing original data from a large‐scale household survey conducted in Costa Rica from October 2013 to April 2014 (n = 4,200), we find that the observation of police violence significantly reduces citizens’ willingness to report crime. The implications of this finding are explored using a game‐theoretic model of crime, crime reporting, and police misconduct. The model reveals that although the prospect of police violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Previous research has shown that witnessing police brutality decreases the likelihood of reporting crimes by reinforcing the belief that police may in fact escalate violence. 26 In today’s digital world, widely circulating images of police violence against Black persons may have reduced trust in police, especially in Chicago, where Black persons account for 74% of fatalities due to police violence but comprise only 29% of the city’s population. 27 Furthermore, many DV survivors are women, 4 and cases of police violence against Black women specifically, may have contributed to an erosion of trust during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that witnessing police brutality decreases the likelihood of reporting crimes by reinforcing the belief that police may in fact escalate violence. 26 In today’s digital world, widely circulating images of police violence against Black persons may have reduced trust in police, especially in Chicago, where Black persons account for 74% of fatalities due to police violence but comprise only 29% of the city’s population. 27 Furthermore, many DV survivors are women, 4 and cases of police violence against Black women specifically, may have contributed to an erosion of trust during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of predictive policing, prior cases of inferior, discriminatory or outright illegal policing ("dirty policing") are visible in criminological data ("dirty data") (Richardson, Schultz and Crawford 2019, p. 192), e. g. due to underreporting of sexual crimes (Taylor and Gassner 2010, p. 241 ff. ), racist crimes (Kushnick 1999, ¶1.7) and police violence (Loftin, McDowall and Xie 2017;Gingerich and Oliveros 2018). Following the legal precepts of non-discrimination in policing and counteracting such biases is made all the harder by the fact that there is often little awareness and acknowledgement of these underlying problems and the discriminatory structures which are (at least partially) responsible therefor.…”
Section: Problems Of Data Society and Technologymentioning
confidence: 99%
“…The low reporting of crime offers further clarity on the nature of crime trends in Ghana. The underreporting of crime is common in instances of rape, homicides, and domestic violence (Feldman et al 2017;Myers 1980;Gingerich and Oliveros 2018;Loftin et al 2003). A 2011/2013 Afrobarometer survey found that 75% of victims of crime in Ghana did not report the crime to the police (Wambua 2015).…”
Section: International Crime Drop In Retrospectmentioning
confidence: 99%